Identification of visitors’ behavior towards the usage of canopy walkway at KL Forest Eco – Park - Abdul Mutalib, Hasnura Hazlin (2019)
The increasing demand for recreation activities in Malaysia shows that people are beginning to be aware about the benefits of recreation either psychologically or physically. However, outdoor recreation activities always pose certain risks that are sometimes ignored by outdoor recreation participants. Due to the fact that the visitors are from different background profiles, they possess different behavior when engaging with recreation activities. The non-compliance behavior of certain group of visitors at this canopy walkway could create potential risk to other visitors. The Forestry Department is yet in the process of enhancing its precaution steps to minimize the potential risks that might occur in the future. This study attempts to determine the level of visitors’ knowledge on the risk awareness when using the canopy walkway at KL Forest Eco-Park. Furthermore, the study also conducted to access the relationship between visitors’ profile and the behavior intention when using the canopy walkway at KL Forest Eco-Park. The study involved 200 respondents, where their level of awareness on risk and behavior intention based on their profile was determined using a self-reported questionnaire. Results showed that the respondents have a medium level of awareness on risk when using the canopy walkway at KL Forest Eco-Park. In particular, visitors’ behavior intentions were influenced by the respondents’ age group, gender, race, nationality and average monthly income. From the study conducted, these background profile shows significance difference in terms of the influencing factor of the behavior intention for non-compliance behavior (running, jumping, blocking and not follow user limit) towards the canopy walkway. Thus, the Forestry Department should take effective steps to control this non-compliance behavior of visitors towards the canopy walkway at KL Forest Eco-Park.